Modeling, Programming and Simulations Using LabVIEW™ Software - De Asmundis, Riccardo (IntechOpen, 2011)
Born originally as a software for instrumentation control, LabVIEW became quickly a very powerful programming language, having some peculiar characteristics which made it unique: the simplicity in creating very effective Users Interfaces and the G programming mode. While the former allows designing very professional controls panels and whole Applications, completed with features for distributing and installing them, the latter represents an innovative and enthusiastic way of programming: the Graphical representation of the code. The surprising aspect is that such a way of conceiving algorithms is absolutely similar to the SADT method (Structured Analysis and Design Technique) introduced by Douglas T. Ross and SofTech, Inc. (USA) in 1969 from an original idea of MIT, and extensively used by US Air Force for their projects. LabVIEW practically allows programming by implementing straightly the equivalent of an SADT "actigram". Beside this academical aspect, LabVIEW can be used in a variety of forms, creating projects that can spread over an enormous field of applications: from control and monitor software to data treatment and archiving; from modeling to instruments controls; from real time programming to advanced analysis tools with very powerful mathematical algorithms ready to use; from full integration with native hardware (by National Instruments) to an easy implementation of drivers for third party hardware. In this book a collection of different applications which cover a wide range of possibilities is presented. We go from simple or distributed control software to modeling done in LabVIEW; from very specific applications to usage in the educational environment.